2021
DOI: 10.1186/s12879-021-06574-x
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for disease progression in Japanese patients with COVID-19 with no or mild symptoms on admission

Abstract: Background Although the risk factors for coronavirus disease 2019 (COVID-19) mortality have been identified, there is limited information about the risk factors for disease progression after hospitalization among Japanese patients with COVID-19 exhibiting no or mild symptoms. Methods All 302 consecutive patients who were admitted to our institutions and diagnosed with COVID-19 between March and December 2020 were retrospectively assessed. Ultimatel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 26 publications
(35 reference statements)
1
10
0
Order By: Relevance
“…Consistent with a lot of previous reports [1] , [11] , [12] , [14] , [16] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , the present study identified that obesity was independently associated with severe status of COVID-19 during hospitalization. Obesity may lead to an impaired immune system and reduced respiratory function [10] , [34] .…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with a lot of previous reports [1] , [11] , [12] , [14] , [16] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , the present study identified that obesity was independently associated with severe status of COVID-19 during hospitalization. Obesity may lead to an impaired immune system and reduced respiratory function [10] , [34] .…”
Section: Discussionsupporting
confidence: 93%
“…37-39 A Japanese study reported that diabetes is an independent risk factor of disease progression in patients with COVID-19 with no or mild symptoms who do not require oxygen administration. 24 These factors can attenuate the immune response, leading to increased susceptibility to viral infections, and exacerbating the infection. In addition to these potential baseline risk factors, comorbidities, and biomarkers, the development of thrombosis was found to be independently and strongly associated with worsening COVID-19 severity in this study, suggesting that more aggressive pharmacological thromboprophylaxis may be helpful for the prevention of worsening COVID-19 severity.…”
Section: Discussionmentioning
confidence: 99%
“…23 A recent Japanese study reported that 49/210 patients (23%) exhibiting no or mild COVID-19 symptoms on admission required oxygen supplementation during hospitalization. 24 The nationwide COVID-19 Registry in Japan (COVIREGI-JP) study reported that mechanical ventilation or ECMO was required during hospitalization in 2.0% of patients with non-severe and 26.4% of patients with severe COVID-19. 25 In this study, 19.6% of patients with moderate COVID-19 upon admission had worsening of COVID-19 severity, which is consistent with previous reports.…”
Section: Incidences Of Thrombosis and Major Bleedingmentioning
confidence: 99%
“…Several previous reports of the risk factors for the disease severity and progression of COVID-19 in Japan have been published. 31 , 32 A recent large-scale Japanese registry-based study that included 3,829 COVID-19 patients reported that male sex, higher age, hypertension, obesity, cardiovascular disease, and diabetes were independent risk factors for disease progression. 17 However, the mortality-associated risk factors for COVID-19 patients in Japan have not been reported.…”
Section: Discussionmentioning
confidence: 99%